2015
DOI: 10.1039/c5ta06069a
|View full text |Cite|
|
Sign up to set email alerts
|

Critical advances for the iron molten air battery: a new lowest temperature, rechargeable, ternary electrolyte domain

Abstract: The iron molten air battery cycled stably at 500 °C for 60 cycles using cost effective nickel and steel electrodes and KCl–LiCl–LiOH eutectic electrolyte with added NaOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Such performance characteristics of MIB closely resemble supercapbatteries. [20,21] This is another advantage of the MIB compared to other electrochemical energy storage devices. Note that the surface area of negative electrode in the MIB is far less than that of carbon-basede lectrodes in supercapbatteries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such performance characteristics of MIB closely resemble supercapbatteries. [20,21] This is another advantage of the MIB compared to other electrochemical energy storage devices. Note that the surface area of negative electrode in the MIB is far less than that of carbon-basede lectrodes in supercapbatteries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many base metalsi ncluding iron, tin, and bismuth can be activateda th igh temperatures and thus utilized to lower the battery cost. [19][20][21] In at ypical MAB, fast iron redox reactions in molten Li 2 CO 3 were proposed as battery reactions for energy storagea nd conversion,w ith a high theoretical specific energy of 1400 Wh kg À1 and energy density of 10 000 Wh L À1 .O fp articulari mportance is that the moltens alts in MAB have the capabilityt od issolve metal oxides. For instance, the high-temperature iron-oxide battery explorest he iron redox reactions in as olid oxide fuel cell (SOFC) structure throughaH 2 /H 2 Om ediator, which performs higherd ischarge capacities in comparison with room-temperature iron-oxygenb atteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group proposed that the reactions in the iron molten air battery are represented using Equation , including Equation showing the dissolution of Fe 2 O 3 by Li 2 O or Na 2 O to form LiFeO 2 or NaFeO 2 , followed by quasi‐reversible charge–discharge of LiFeO 2 or NaFeO 2 to iron, as shown in Equation 1 / 2 Fe 2 normalO 3 Fe + 3 / 4 normalO 2 …”
Section: Introductionmentioning
confidence: 99%
“…Based on the three‐electron oxidation of iron, the theoretical specific energy density of iron molten air batteries is 1440 A h kg −1 . However, our previous attempts have demonstrated that one of the biggest challenges facing practical applications is the sluggish oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) kinetics …”
Section: Introductionmentioning
confidence: 99%